Renal function, cardiovascular disease and long term outcome in different cohorts of the Glasgow population - Murphy, Aengus (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2011)
Over the past ten to fifteen years, the interaction between cardiovascular disease and chronic kidney disease (CKD) has come under increased scrutiny. Traditional cardiovascular risk factors are also associated with the onset of kidney disease whilst even milder forms of renal disease have been shown to independently predict adverse outcome in a number of different populations, particularly cardiovascular death. Over the past 5 years, change in renal function over time has been increasingly studied in an attempt to further understand cardio-renal interaction.
Keywords: Clinical Medicine, M.D.; M.D. Trinity College Dublin